Cardiac Involvement in Patients With Multisystem Inflammatory Syndrome in Adults - Giulia La Vecchia; Marco Giuseppe Del Buono; Aldo Bonaventura; Alessandra Vecchiè; Francesco Moroni; Iside Cartella; Gianluigi Saponara; Michael J. Campbell; Lorenzo Dagna; Enrico Ammirati; Tommaso Sanna; Antonio Abbate (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Multisystemic inflammatory syndrome in adults is a hyperinflammatory condition following (within 4–12 weeks) SARS‐CoV‐2 infection. Here, the dysregulation of the immune system leads to a multiorgan involvement often affecting the heart. Cardiac involvement in multisystemic inflammatory syndrome in adults has been described mainly in young men without other comorbidities and may present with different clinical scenarios, including acute heart failure, life‐threatening arrhythmias, pericarditis, and myocarditis, with a nonnegligible risk of mortality (up to 7% of all cases). The heterogeneity of its clinical features and the absence of a clear case definition make the differential diagnosis with other postinfectious (eg, infective myocarditis) and hyperinflammatory diseases (eg, adult Still disease and macrophage activation syndrome) challenging. Moreover, the evidence on the efficacy of specific treatments targeting the hyperinflammatory response underlying this clinical condition (eg, glucocorticoids, immunoglobulins, and other immunomodulatory agents) is sparse and not supported by randomized clinical trials. In this review article, we aim to provide an overview of the clinical features and the diagnostic workup of multisystemic inflammatory syndrome in adults with cardiac involvement, highlighting the possible pathogenetic mechanisms and the therapeutic management, along with remaining knowledge gaps in this field.